Proceedings of the 5th International Conference on the Durability of Concrete Structures 2016
DOI: 10.5703/1288284316126
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Disposition of Water in Fly Ash-Based Geopolymers Using ATR–IR

Abstract: This paper addresses the question of whether the main product of low calcium fly ash-based geopolymer is a hydrate, namely, sodium aluminosilicate hydrate (N-A-S-H). The answer to this question is important for understanding geopolymer characteristics. One of these is its fire resistance. In this study, fly ash-based geopolymers were synthesized using the combination of Na 2 CO 3 and Ca(OH) 2 . Samples were cured at ambient temperature for 7 days, then placed in the oven at 105°C for 24 h, and then calcined at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…He demonstrates that calcium or sodium hydrates are soluble in water and will not form any polymer to bind the materials in the system. Prof Davidovits observation finds an agreement with Liu et al 25 They reported that the produced geopolymer is not primarily comprise of C‐S‐H or N‐A‐S‐H or C‐A‐S‐H as the backbone of geopolymer chemistry. Although higher amount of CaO in the base material like GGBFS can leads to the development of C‐A‐S‐H and C‐S‐H gel 26 but they will coexist with geopolymer in the system 27 .…”
Section: Experimental Programsupporting
confidence: 80%
“…He demonstrates that calcium or sodium hydrates are soluble in water and will not form any polymer to bind the materials in the system. Prof Davidovits observation finds an agreement with Liu et al 25 They reported that the produced geopolymer is not primarily comprise of C‐S‐H or N‐A‐S‐H or C‐A‐S‐H as the backbone of geopolymer chemistry. Although higher amount of CaO in the base material like GGBFS can leads to the development of C‐A‐S‐H and C‐S‐H gel 26 but they will coexist with geopolymer in the system 27 .…”
Section: Experimental Programsupporting
confidence: 80%
“…In the study by Davidovits, it is even pointed out that a geopolymer is not a hydrate. Liu and Fang found that there is no or very little chemical water in N‐A‐S‐H. These results can indicate that the water consumption during the geopolymerization is much lower than in the hydration of Portland cement.…”
Section: Resultsmentioning
confidence: 99%